Associative-semantic certainty of response to verbal stimuli secular and religious values - Гарник Владимирович Акопов; Светлана Геннадьевна Ихсанова; Татьяна Константиновна Рулина (Rossijskij psihologičeskij žurnal., 2015)
This paper deals with the problem of religious consciousness in modern Russia. Religious consciousness is understood as unit of categories reflecting system of religious and ecclesiastical traditions. To study used associative experiment, which allows you to identify the semantic links between the studied categories and based on them to build a semantic field. The study used the classical scheme of the association experiment, based on the presentation of pre-selected words stimuli causing verbal reactions of the subjects. The thematic content of the stimulus series allowed us to obtain verbal responses expressing semantic and emotional attitude of study participants to concepts such as “faith”, “mercy”, “contemplation”, “act” and others. Such stimulation affected the deepest layers of the national consciousness of Russians. The empirical part of the work is two pieces of large-scale study of consciousness, performed at the Faculty of Psychology of the Volga State Academy of Socio-Humanitarian. One shows the associative structure of the religious consciousness of older rural residents with deep religious roots. In another – semantic field of concepts “contemplation”, “act”, “communication”, obtained on a sample of students. Comparative analysis of the results allows coming to consistent conclusions about the mechanisms of change semantic fields. One such mechanism is the hyper-event – a significant fact of reality that affects the awareness of related categories. The article raised the question of interpenetration phenomena of religious consciousness and contemplation. The results obtained, as well as their qualitative and quantitative analysis suggests that the mind of modern man does not bind directly to religious categories and categories of phenomenological contemplation. This fact indicates the nature of the non-religious contemplation and meditation allows us to consider a category as an independent scientific unit.